How Can I Find My Ride? Importance of User Assistance in Finding Virtual Stops for Shared Autonomous Mobility-on-Demand Services - Malte Petersen; Andreas Zuck; Annika Dreßler (Future Transportation)
Future mobility concepts, such as Shared Autonomous Mobility-on-Demand (SAMOD) services, have the potential to contribute to sustainability goals and enhance connectivity between rural areas and urban public transport networks. The SAMOD concept relies on virtual stops, accessible via a smartphone application, where passengers are individually picked up. This study analyzed the importance of six key attributes of a SAMOD journey: travel time, price, available information, distance to the stop, navigation to the virtual stop, and identification of the virtual stop. Using a choice-based conjoint analysis (N = 461), participants were repeatedly presented with two SAMOD journey options, each varying in attributes, and were asked to indicate their preference. The findings reveal that all six attributes significantly influenced travel decisions. Subgroup analyses further indicated that the importance of these attributes varied by gender, age, travel context, and frequency of public transport use. Notably, SAMOD-specific attributes, such as navigation to and identification of the virtual stop, were rated as nearly as critical as traditional factors like travel time and cost. Based on these findings, actionable recommendations for transport planners and policymakers are proposed to facilitate the successful implementation of SAMOD services.